Effect of Freezing-Thawing Cycles on the Physical and Mechanical Properties of Some Sedimentary Rocks Located Near Mosul City - Thamer Mohammed Nuri; Moafaq Abbo Awad; Asaad Mohamad Azhar Msbah (Engineering and Technology Journal, 2011)
This study is aimed to investigate the surfacial deterioration of some common sedimentary rocks near Mosul city as a result of freezing-thawing cycles on physical and mechanical properties of two types of Limestone denoted as (L1 and L2), Sandstone (S) and Mosul Marble (M). Physical and mechanical tests include; uniaxial, triaxial compression tests, point load test and the indirect tensile strength(Brazilian test) have been performed on both the fresh specimens and the specimens subjected to a number of freezing-thawing cycles (5, 10, 15 and 20). Test results showed that the freezing and thawing is a process of physical deterioration, a significant reduction in different percentages in uniaxial and triaxial compressive and tensile strength was observed in all the rocks tested. A little variation was observed inthe slaking durability indices (IS-D) of (L1, L2 and M) rocks among three conducted cycles at fresh state, while (S) rock showed high percent loss of about 45.81% in its durability. On the other hand, the water absorption percent of the tested rocks showed a clear increase with the increase of number of freezing-thawing cycles.